Location strategies for proximity supermarkets: A case study of Carrefour and Marjane in Morocco - Nouha, Ben Aissa; Mahmoud, Belamhitou (Edelweiss Applied Science and Technology, 2025)
Location is an essential factor in urban supermarkets that impacts their attraction and sales performance. In a fast-changing market, supermarket chains should adjust their location strategies to improve coverage and meet consumer expectations. In this context, the purpose of this study is to examine the location strategies of Carrefour (Label’Vie) and Marjane Holding in Morocco, highlighting the factors impacting their location decisions. To achieve this objective, a case study approach is adopted, based on secondary data (company reports, academic publications, and sector studies). The methodology relies on theoretical models of retail location, including Central Place Theory (Christaller), the Huff Model, and the Theory of Spatial Consumer Behavior, which help elucidate store distribution and competitive dynamics. The findings reveal that geographical, socio-economic, and competitive factors play a decisive role in supermarket location choices. Additionally, the results highlight the greater importance of digitalization and adaptation to new shopping behaviors. In conclusion, this study provides a conceptual framework for optimizing location strategies in a rapidly evolving retail landscape. From a practical perspective, the insights gained can help retail decision-makers refine their expansion strategies by integrating digital transformation and evolving consumer behaviors into their location planning.